Promoting global competencies through media literacy - Yildiz, Melda N., 1969-; Funk, Steven S.; De Abreu, Belinha S. (Information Science Reference, 2018)
"This book provides K-16 educators assessment tools and strategies that are transformative and transdisciplinary and highlight best practices for 21st century classrooms. It provides a wide range of strategies and frameworks to empower educators, teacher candidates, and educational researchers to examine the benefits, challenges, and opportunities of integrating educational assessment and evaluation into media literacy education"--